The last trip of bishop Lisson - Arrizabalaga, Carlos (Mercurio Peruano, 2016)
25 years ago, on August 1, 1991, the Archbishop of Valencia, Don Miguel Roca Cabanellas, arrived in Lima accompanying the mortal remains of Monsignor Emilio Lissón Chávez, which were transferred from the Cathedral of Valencia to that of Lima.